Vibration cause analysis and elimination of reciprocating compressor inlet pipelines. (February 2015) - Liang, Zheng; Li, Shuangshuang; Tian, Jialin; Zhang, Liang; Feng, Chengke; Zhang, Liwen
Highlights: The root vibration cause of the inlet pipelines was obtained by modal analysis and velocity frequency spectrum analysis. The first six natural frequencies of the pipelines were obtained by finite element modal analysis and experimental modal test using hammering method. The vibration level of pipelines was estimated by harmonic analysis and site vibration measurements. The pipelines vibration was controlled by enlarging the buffer volume of gathering manifold and adjusting the inlet piping length. Abstract: Due to the occurrence of abnormal vibration of reciprocating compressor inlet pipelines during the commissioning of a booster station, the cause of severe vibration problem was investigated, which included modal analysis, calculation of resonant piping length, velocity frequency spectrum analysis, and pressure pulsation measurement. It was found that the inlet pipelines avoided low frequency resonance region, the actual length of the inlet pipelines was in the second resonant piping length, and the pressure pulsation far exceeded API 618 standard. The results indicate that large pressure pulsation and acoustic resonance occurred on the inlet pipelines are the key factors inducing vibration. Vibration elimination treatments included enlarging the buffer volume of gathering manifold, adjusting the inlet piping length to avoid acoustic resonance, and increasing the curvature radius of bend. After remodeling of the inlet pipelines, the test data indicate that the vibration level of the inlet pipelines is reduced to an acceptable level defined by a relevant standard, and the processing capacity of the booster station can be raised at least two times.